P4-S1.05 Polymerase chain reaction-based typing of penA genes exhibiting elevated MIC values to cephalosporins in Isolates of Neisseria gonorrhoeae. (10th July 2011) - Trees, D; Burroughs, M; Harris, S; Johnson, S
Abstract : Objective: Develop a PCR based assays for rapid analysis of isolates that exhibit elevated MIC values to penicillin and cephalosporins (MICs of 0.015–0.06 ug/ml to ceftriaxone). These primers were designed to detect mosaic and nonmosaic sequences in the penA gene. Methods: Two sets of primer pairs were generated that allowed the detection of mosaic-type and nonmosaic-type penA gene sequences in isolates of N gonorrhoeae that exhibited elevated MIC values to three cephalosporins. Additional primer sets were generated that detected the presence of an inserted aspartic acid residue in nonmosaic penA genes involved in resistance and to detect base substitutions to distinguish between two different mosaic penA genes. DNA sequences were determined as necessary by standard sequencing or pyrosequencing. Results: PCR analysis of 28 isolates, exhibiting elevated MIC values to cephalosporins and from different geographic areas, that used these primer sets in combination allowed for the detection of mosaic penA genes in 12 isolates. The remaining isolates possessed nonmosaic genes. Not all of the 12 isolates contained complete mosaic-type sequences with five of the isolates indicating mosaic sequences present in the 5′ region of the penA gene with wild type DNA sequence replacing the last 120 bp of the gene. Another isolate contained nonmosaic penA sequences with an aspartic acid insertion (after aa 345) in the 5′ region of the gene but mosaic sequences in the 3′ end. Finally, mosaic-related sequences were detected by PCR and confirmed by DNA sequencing in the last 106 base pairs of the penA gene of a penicillin sensitive strain isolated prior to 1976. Conclusion: PCR can be used to easily detect the presence of mosaic penA genes in isolates of N gonorrhoeae . This study has shown the 3′ region of the gene may contain mosaic, partial mosaic and nonmosaic-type sequences and that mosaic-type sequence has been encountered in the 3′ region of penA in a sensitive strain. We have also observed isolates with increased MICs to cephalosporins that do not contain mosaic sequences. Finally, isolates that possess mosaic penA genes have been detected in dispersed geographic regions in the US, which is of concern due to the evidence mosaic-type penA alleles are involved in the process of increasing gonococcal MICs to cephalosporins.